Physiology of Saliva: An Overview - Pandey, Abhay K (Journal of Dentistry Indonesia, 2014)
and living condition as well as eating habit would influence salivary function. Saliva palys a role in determining the development pattern and oral health. Saliva has a unique function in the defense mechanism to microorganism in the oral environment. Research focuses on the salivary physiology is limited and seems to be separated from medical and dental professional education. Better and deeper comprehensive understanding of saliva in health and disease is needed. Nowadays, many studies have used saliva to find diagnosis markers for specific diseases. Salivary analysis is intended to give descriptive information on disease status for prevention, monitoring and treatment purposes. This brief review aimed to give understanding on salivary physiology in order to add new views of its application in the field of medicine and dentistry.